Azithromycin for infants at risk of poor growth and development: A pooled secondary analysis of two randomized controlled trials - Mamadou Bountogo; Mamadou Ouattara; Clarisse Dah; Boubacar Coulibaly; Thierry Ouedraogo; Alphonse Zakane; Valentin Boudo; Elodie Lebas; Huiyu Hu; Benjamin F. Arnold; Thomas M. Lietman; Ali Sié; et al. (PLoS ONE, 2025)
Background In 2023, the World Health Organization (WHO) revised its guidelines for management of severe acute malnutrition (SAM). The revised guidelines include a focus on infants at risk of poor growth and development. The guideline identifies evaluation of routine antibiotics for these infants as a priority research area. Objective We pooled data from two large randomized controlled trials evaluating azithromycin for prevention of infant mortality in Burkina Faso to assess whether azithromycin reduces mortality or wasting in this subgroup. Methods Infants in the two trials were 1–12 weeks of age at enrollment. Infants were considered at risk of poor risk of growth and development per WHO: underweight (weight-for-age Z-score, WAZ < −2), wasted (weight-for-length Z-score, WLZ < −2), or MUAC < 11.0 cm among infants ≥6 weeks of age. Infants were randomized to a single oral (20 mg/kg) dose of azithromycin or matching placebo and were followed until 6 months of age. We evaluated vital status, underweight (WAZ < −2), wasting (WLZ < −2), and stunting (length-for-age Z-score, LAZ) at 6 months among infants at risk of poor growth and development based on WHO single measurement criteria. Results A total of 54,709 infants were enrolled in the two trials. Of these, 9,728 were at risk of poor growth and development based on baseline WAZ (N = 5,385), WLZ (N = 6,022), or MUAC (N = 1,541). We found no evidence of a difference in mortality (1.3% vs 1.1%, odds ratio, OR, 1.19, 95% confidence interval, CI, 0.82 to 1.72) or wasting (20.6% vs 20.2%, OR 1.03, 95% CI 0.92 to 1.14) at 6 months among infants receiving azithromycin versus placebo. Conclusions In infants aged 1–12 weeks at risk of poor growth and development, we do not have evidence that single dose azithromycin reduces mortality or improves growth outcomes. Trial registration ClinicalTrials.gov NCT03682654 and NCT03676764.